Autonomy and enhancement - Schaefer, G; Kahane, G; Savulescu, J (Springer Netherlands, 2014)
Some have objected to human enhancement on the grounds that it violates the autonomy of the enhanced. These objections, however, overlook the interesting possibility that autonomy itself could be enhanced. How, exactly, to enhance autonomy is a difficult problem due to the numerous and diverse accounts of autonomy in the literature. Existing accounts of autonomy enhancement rely on narrow and controversial conceptions of autonomy. However, we identify one feature of autonomy common to many mainstream accounts: reasoning ability. Autonomy can then be enhanced by improving people’s reasoning ability, in particular through cognitive enhancement; given how valuable autonomy is usually taken to be, this gives us extra reason to pursue such cognitive enhancements. Moreover, autonomy-based objections will be especially weak against such enhancements. As we will argue, those who are worried that enhancements will inhibit people’s autonomy should actually embrace those enhancements that will improve autonomy.